ESTIMATION OF SOME GENETIC PARAMETERS OF GROWTH AND YIELD CHARACTERS OF SUNFLOWER UNDER THREE PLANT DENSITIES - Hassan, W.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
To know the genetic variations for some sunflower (Helianthus annuus L.) traits under the influence of three plant population (40000, 50000 and 60000 plants.ha-1) for tow varieties (oil and non-oil) of sunflower. The experiments were conducted during spring and fall seasons of 2013, using factorial experiment within RCBD. The plant spaces between the furrows 90 cm and within furrows 27.8, 22.2 and 18.5 cm, which variable due to plant population. The field was fertilized using compound fertilizer (18% N: 18% P2O5) and urea (46%N)at 350 kg. ha-1. The results revealed that there are genotypic and phenotypic homogeneity in both varieties, according to the lowest S , CV, GCV and PCV for most of studied traits. The broad sense heritability values (83-98%) and the 60000 plant population in fall season for most of traits that cause to increase genetic gain (16-42%). It was concluded that number of seeds.head-1 and seeds weight can be used as selection index to improve both varieties.